Prevalence and the predictive performance of the dynamic CT-angiography spot sign in an observational cohort with intracerebral hemorrhage. Issue 47 (20th November 2020) - Dowlatshahi, Dar; Chung, Hee Sahng; Reaume, Michael; Hogan, Matthew J.; Blacquiere, Dylan; Stotts, Grant; Shamy, Michel; Momoli, Franco; Aviv, Richard; Demchuk, Andrew M.; Chakraborty, Santanu
Abstract : Abstract: The CT-angiography (CTA) spot sign is a predictor of hematoma expansion (HE). We have previously reported on the use of dynamic CTA (dCTA) to detect spot sign, and to study its formation over the acquisition period. In this study, we report the frequency of dCTA spot sign in acute intracerebral hemorrhage, its sensitivity and specificity to predict HE, and explore the rate of contrast extravasation in relation to hematoma growth. We enrolled consecutive patients presenting with primary intracerebral hemorrhage within 4.5 hours. All patients underwent a dCTA protocol acquired over 60 seconds following contrast injection. We calculated frequency of the dCTA spot sign, predictive performance, and rate of contrast extravasation. We compared extravasation rates to the dichotomous definition of significant HE (defined as 6 mL or 33% growth). In 78 eligible patients, dCTA spot sign frequency was 44.9%. In 61 patients available for expansion analysis, sensitivity and specificity of dCTA spot sign was 65.4% and 62.9%, respectively. Contrast extravasation rate did not significantly predict HE (Odds Ratio 15.6 for each mL/min [95% confidence interval 0.30–820.25], P  = .17). Correlation between extravasation rate and HE was low ( r  = 0.297, P = .11). Patients with significant HE had a higher rate of extravasation as compared to those without (0.12 mL/min vs 0.04 mL/min, P  = .03). Dynamic CTA results in a higher frequency of spot sign positivity, but with modest sensitivity and specificity to predict expansion. Extravasation rate is likely related to HE, but a single measurement may be insufficient to predict the magnitude of expansion.